2017
DOI: 10.1002/ijgo.12175
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and vertical transmission of human pegivirus among pregnant women infected with HIV

Abstract: Prenatal care could protect against vertical transmission of HPgV among women infected with HIV; however, studies among HIV-negative individuals are still required to verify this correlation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 28 publications
(68 reference statements)
0
12
1
Order By: Relevance
“…The prevalence of HPgV among the individuals diagnosed with HIV-1 in this study was 9,7% higher than that reported by Miranda et al [38]. The high prevalence of HPgV among HIV-1 individuals has been reported in several studies in Brazil and the world [40][41][42]. The association between the presence of HPgV and HIV is owing to the fact that HPgV likely acts as a protective factor for the development of HIV [40,43,44].…”
Section: Discussioncontrasting
confidence: 43%
“…The prevalence of HPgV among the individuals diagnosed with HIV-1 in this study was 9,7% higher than that reported by Miranda et al [38]. The high prevalence of HPgV among HIV-1 individuals has been reported in several studies in Brazil and the world [40][41][42]. The association between the presence of HPgV and HIV is owing to the fact that HPgV likely acts as a protective factor for the development of HIV [40,43,44].…”
Section: Discussioncontrasting
confidence: 43%
“…HPgV-1 can be transmitted through parenteral, sexual, or motherto-child routes. [16][17][18][19] Coinfection with HIV or hepatitis C virus (HCV) is common due to shared transmission modes and also in those exposed to transfused blood products, transplanted patients, injection drug users, hemophiliacs, and patients requiring hemodialysis. 20 In the general population, the prevalence of HPgV-1 ranges from 1% to 4% in North America and Europe and from 5% to 19% in Africa, Asia, and South America.…”
mentioning
confidence: 99%
“…This reduced prevalence of HPgV-1 infection compared to most reported papers in the literature may be explained by the method used (only viral RNA was used for diagnosis) [7,14,21,26] and a more advanced age. Individuals between 18 to 30 and 31 to 50 years are approximately eight and six times, respectively more prone to show HPgV infection than those older than 50 years [19].…”
Section: Plos Onementioning
confidence: 71%
“…Other studies have also investigated the prevalence of HPgV-1 in healthy blood donors in the South Region, and the results indicated a seroprevalence between 5.9% [6] and 21.7% [19]. In people living with HIV, the prevalence of HPgV-1 infection was 34% [20], and vertical transmission of HPgV-1 in pregnant women with HIV was 31% [21].…”
Section: Plos Onementioning
confidence: 99%